Orthostatic hypertension in cardiovascular risk stratification in hypertensive patients - E. Yu. Gubareva; O. V. Fatenkov; I. V. Gubareva; D. A. Klimenko; L. Yu. Shvan; L. V. Limareva (Российский кардиологический журнал)
Hypertension (HTN) is an important modifiable risk factor for cardiovascular disease associated with poor outcomes and high health care costs. The assessment of cardiovascular risk (CVR) according to the current ESC/ESH guidelines for the treatment of hypertensive patients presents a number of difficulties and initiates the search for new diagnostic methods that contribute to understanding the patient's phenotype, personalizing diagnostic and treatment tactics, and improving the outcomes of hypertensive patients. Regulatory mechanisms involved in the body's orthostatic response, such as activation of the sympathetic nervous system, catecholamine production, endothelial function, significantly contributes to maintaining blood pressure levels. Their violation plays an active role in hypertension development, which allows considering orthostatic HTN in a hypertensive patient as a marker of CVR stratification. The article discusses the diagnostic criteria for orthostatic HTN, its pathophysiological mechanisms and possible use as a marker of CVR stratification.